Behavior of large-scale FRP-confined rectangular RC columns under eccentric compression. (1st August 2020) - Lin, Guan; Zeng, J.J.; Teng, J.G.; Li, L.J.
Highlights: Large-scale eccentrically-loaded FRP-confined rectangular RC columns were tested. A theoretical model is presented for such columns. The use of a concentric-loading stress-strain model leads to significant errors. The development of an eccentric-loading stress-strain model is needed. Abstract: Fiber-reinforced polymer (FRP) composites have become widely accepted in the strengthening or seismic retrofitting of reinforced concrete (RC) columns in practice. FRP-confined rectangular concrete columns under concentric axial compression have been extensively studied, leading to many stress-strain models (i.e., concentric-loading stress-strain models). Although RC columns in practical structures are commonly subjected to combined axial compression and bending (i.e., eccentric compression), existing research on eccentrically-loaded FRP-confined rectangular RC columns has been much more limited. More specifically, the limited research available has generally been concerned with small-scale RC columns, and the applicability of existing concentric-loading stress-strain models for FRP-confined concrete in the analysis of large-scale eccentrically-loaded rectangular RC columns has not been properly clarified. This paper presents the results of an experimental study including eight large-scale FRP-confined rectangular RC columns tested under eccentric compression. The following key test variables were carefully examined in the experimental program: the load eccentricity, the direction of bending, and the FRP jacket thickness. A theoretical column model is then presented for predicting the responses of the test columns. It is shown that the direct use of a concentric-loading stress-strain model for FRP-confined concrete in the column model leads to significant errors in predicting the ultimate deformation of the test columns.